Development and evaluation of sustained release alginate beads containing tetrahydrocurcumin and curcumin - Sirirat Sriraksa (Prince of songkla university, 2014)
Thesis (M.Pharm., Pharmaceutical Sciences)--Prince of Songkla University, 2014